2012
DOI: 10.1007/s00280-012-1874-2
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in solid tumors

Abstract: Monitoring of blood counts and for evidence of thromboembolic events is essential for patients treated with lenalidomide. Ongoing trials of lenalidomide combination therapy offer a treatment option for patients with advanced cancer and will better define the role of lenalidomide in solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…21 Lenalidomide inhibits growth of many hematologic cell lines 21 and is currently being used in clinical trials to treat various hematologic malignancies and solid tumors. [22][23][24][25] In particular, lenalidomide has shown promise in several studies in patients with NHL (not including CTCL), including in patients with relapsed/refractory disease. [26][27][28][29] Despite the rationale for using lenalidomide in patients with CTCL, data on this treatment approach are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…21 Lenalidomide inhibits growth of many hematologic cell lines 21 and is currently being used in clinical trials to treat various hematologic malignancies and solid tumors. [22][23][24][25] In particular, lenalidomide has shown promise in several studies in patients with NHL (not including CTCL), including in patients with relapsed/refractory disease. [26][27][28][29] Despite the rationale for using lenalidomide in patients with CTCL, data on this treatment approach are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…IMiDs (such as thalidomide and lenalidomide, which are used in multiple myeloma and non-Hodgkin lymphoma) and TKIs (such as imatinib, nilotinib and dasatinib, which are used in chronic myeloid leukemia) have also antiangiogenic properties (3). Among side effects of IMIDs and TKIs, alteration of thyroid function and triggering of thyroid autoimmunity has been reported (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Side effects on the thyroid caused by head and neck radiotherapy include altered function and development of nodules that are at greater risk of being malignant (14).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid investigations in patients with hematological disorders have essentially focused on the thyroid complications ensuing from chemotherapy and/or external irradiation (4)(5)(6)(7)(8)(9)(10)14,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Because no study has simultaneously taken care of all clinically relevant thyroid aspects (namely, function, autoimmunity and nodules), we have conducted such a study on hematoncologic patients excluding those who had been treated with external irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Recent studies have demonstrated that lenalidomide has activity in a variety of solid tumors, although its efficacy as a single agent is modest. [4] The activity of lenalidomide against solid tumors could be enhanced by combining it with other anti-cancer agents, including other anti-angiogenic drugs. A few studies have indicated that lenalidomide can be safely combined with cytotoxic chemotherapy, with possible synergistic effects.…”
Section: Introductionmentioning
confidence: 99%